The Impact of Different Strain Rates of Polypropylene Geotextiles on Slope Factor of Safety - Sitek Wiktor; Kiersnowska Agnieszka; Bagdasaryan Vazgen; Koda Eugeniusz (Studia Geotechnica et Mechanica, 2025)
Due to their effectiveness, environmental friendliness, and economic benefits, geosynthetics are increasingly utilized in civil engineering, especially woven geotextiles for soil stabilization reinforcement. Standard strength testing assumes a constant rate of elongation for samples, but in practice, the loading rate of geosynthetics in the field is much lower. Selecting appropriate materials is crucial for the effectiveness and durability of structures. For polymeric materials like woven geotextiles, the strain rate affects their properties. Understanding these properties is essential for safe design and construction. This article explores the potential application of polypropylene geotextiles for soil reinforcement in embankments. The polymer properties are discussed, along with the methodology for strength testing of geosynthetics and the results of the research. The findings allowed for the calculation of the long-term strength of samples at different elongation rates, which was used to verify changes in the factor of safety for a slope model. The highest tensile strength was 33.44 kN/m at a stretching speed of 20 mm/min. At 2 mm/min, it was 30.35 kN/m, and at 0.2 mm/min, it was 28.70 kN/m. These results determined the factor of safety: F = 2.08 for the fastest stretched sample and F = 1.97 for the slowest. Theoretical approaches to understanding changes in strength parameters due to variations in strain rate have been presented, as well as computational approaches using the Bishop method in GEO5 software, based on the results from tensile strength tests.